The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0333102416641665
|View full text |Cite
|
Sign up to set email alerts
|

The altered right frontoparietal network functional connectivity in migraine and the modulation effect of treatment

Abstract: Aims This study aims to investigate resting-state functional connectivity (rs-fc) of the right frontoparietal network (rFPN) between migraineurs and healthy controls (HCs), and how the rFPN rs-fc can be modulated by effective treatment. Methods One hundred patients and forty-six matched HCs were recruited. Migraineurs were randomized to verum acupuncture, sham acupuncture, and waiting list groups. Resting state fMRI data was collected before and after longitudinal treatments. Results Independent component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 65 publications
(116 reference statements)
4
72
0
1
Order By: Relevance
“…The abstract does not provide sufficient information but based on background information available to one of us (KL) it seems likely that the trial will meet our eligibility criteria when a full publication with final data becomes available. A second trial originating from China (Li 2016) was published in February and April 2016 after all analyses for this review had been completed. The two publications focus on functional magnetic resonance imaging (fMRI) outcomes but also report headache frequency data for participants completing all fMRI measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The abstract does not provide sufficient information but based on background information available to one of us (KL) it seems likely that the trial will meet our eligibility criteria when a full publication with final data becomes available. A second trial originating from China (Li 2016) was published in February and April 2016 after all analyses for this review had been completed. The two publications focus on functional magnetic resonance imaging (fMRI) outcomes but also report headache frequency data for participants completing all fMRI measurements.…”
Section: Resultsmentioning
confidence: 99%
“…As it is reported, chronic pain is a strong disruptor of intranetwork FC within the DMN, SN, RFPN, and ECN. [ 14 , 15 , 17 , 20 ] These GCA findings suggest that brain functional networks may be performed interactively in encoding different aspects of pain. We speculate that these effects of MwoA on the functional networks may reveal the underlying neural mechanism that pain can be modulated by important causal links in cognitive networks.…”
Section: Discussionmentioning
confidence: 94%
“…[ 12 , 13 ] As for regional resting-state networks, previous studies demonstrated that migraine without aura (MwoA) patients had the abnormal functional connectivity within the default mode network (DMN), [ 14 ] executive control network (ECN), [ 15 ] sensorimotor network (SMN), [ 16 ] salience network (SN), [ 17 , 18 ] periaqueductal gray network, [ 19 ] and right-frontoparietal network (RFPN). [ 20 ] The DMN, RFPN, ECN, and left-frontoparietal network (LFPN) are related to cognition, and potentially associated with pain processing. As the insula is core regions of the SN, SN is also assumed to play a vital role in processing pain.…”
Section: Introductionmentioning
confidence: 99%
“…Tessitore et al 7 studied executive control network functional connectivity and found lower connectivity in the middle frontal gyrus and anterior cingulate cortex in patients with EM. Li et al 13 investigated RSFC of the right frontoparietal network and found that precuneus RSFC with the bilateral rostral anterior cingulate cortex, medial prefrontal cortex, ventral striatum, and dorsolateral prefrontal cortex was significantly enhanced in patients with EM after acupuncture. Schwedt et al 16 investigated effective pain-processing brain regions and demonstrated that patients with CM had significantly lower RSFC of the anterior cingulate cortex, insula, and precuneus.…”
Section: Discussionmentioning
confidence: 99%